2018
DOI: 10.2134/jeq2017.12.0464
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Manure Placement in a Snowpack Affect Nutrient Release from Dairy Manure during Snowmelt

Abstract: Agricultural nutrient management is an issue due to N and P losses from fields and water quality degradation. Better information is needed on the risk of nutrient loss in runoff from dairy manure applied in winter. We investigated the effect of temperature on nutrient release from liquid and semisolid manure to water, and of manure quantity and placement within a snowpack on nutrient release to melting snow. Temperature did not affect manure P and NH-N release during water extraction. Manure P release, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…This is likely due to a low runoff ratio for this event (0.02, ?26 mm of rain and snowmelt water and 0.4 mm of runoff ) compared with the next three events (runoff ratios of 0.45 to 0.84) (Table 1). It may also be due to a lower than typical rate of manure P release by snowmelt water compared with what we have observed for other manures in our research (see Vadas et al, 2018, and discussion about SurPhos modeling assumptions below). For the December 2016 application on CT plots, runoff did not occur until 10 January, and runoff dissolved P for this and the next two events (average of 0.97 mg L −1 ) was three to four times less than runoff P from the NT plots for the same dates (Fig.…”
Section: Decmentioning
confidence: 38%
See 4 more Smart Citations
“…This is likely due to a low runoff ratio for this event (0.02, ?26 mm of rain and snowmelt water and 0.4 mm of runoff ) compared with the next three events (runoff ratios of 0.45 to 0.84) (Table 1). It may also be due to a lower than typical rate of manure P release by snowmelt water compared with what we have observed for other manures in our research (see Vadas et al, 2018, and discussion about SurPhos modeling assumptions below). For the December 2016 application on CT plots, runoff did not occur until 10 January, and runoff dissolved P for this and the next two events (average of 0.97 mg L −1 ) was three to four times less than runoff P from the NT plots for the same dates (Fig.…”
Section: Decmentioning
confidence: 38%
“…SurPhos uses the following equation to estimate WEP release from manure during a rain or snowmelt event: WEPnormalI released ={1.2[W/(W+73.1]}(manure WEPnormalI) where W is the ratio of water volume (rain and/or snowmelt) to manure mass (cm 3 g −1 ). In laboratory experiments using the liquid dairy manure from the same source as used in the field study, Vadas et al (2018) found that Eq. [1] greatly ovepredicted WEP release at lower W values (<150).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations